Altered Expression of IFN-λ2 in Allergic Airway Disorders and Identification of Its Cell Origins. (11th January 2016) - Wang, Qiuli; Chen, Dong; Xie, Hua; Lin, Xiaoping; Wang, Xuefeng; Yao, Qijian; Zheng, Xiaoxuan; Xu, Chiyan; Chen, Lingfei; He, Shaoheng; Zhang, Huiyun
Abstract : This study investigated the expression levels of interferon- (IFN-) λ 2 in peripheral blood and tissues. The results showed that the levels of IFN- λ 2 were elevated by 17.9% and 14.2% in the plasma of allergic rhinitis (AR) and combined rhinitis with asthma (AR + AS), which was positively correlated with the level of tryptase but negatively correlated with the level of IL-10. IFN- λ 2 was predominately expressed in the CD16+ cells and CD14+ cells in healthy control subjects (HC) but upregulated only in CD8+ cells of AR and in eosinophils of asthma. It was observed that approximately 6.6% and 7.0% dispersed tonsil cells and 5.8% and 0.44% dispersed lung cells are IFN- λ 2+ mast cells and macrophages. Moreover, tryptase and agonist peptides of PAR-2 induced enhanced IFN- λ 2 mRNA expression in A549 cells. In conclusion, the elevated levels of IFN- λ 2 in the plasma of AR and AR + AS indicate that IFN- λ 2 is likely to contribute to the pathogenesis of allergic airway disorders. The potential origins of the elevated plasma IFN- λ 2 include mast cells, macrophages, and epithelial cells in tissues, neutrophils, monocytes, CD8+ T cells, and eosinophils in peripheral blood. Development of IFN- λ 2 related therapy may help to treat or prevent allergic airway disorders.